Nouvelle méthodologie d’analyse bayésienne du report des voix et de l’abstention lors du deuxième tour des élections - Girondot, Marc (Comptes Rendus. Mathématique)
The mechanism for deferring votes in two-round elections is a big unknown: does the voter follow a voting instruction, when there is one, or does he develop a personal voting strategy? The information from the counts of the first and second rounds is used to model voter behavior as an inverse problem solved using a Bayesian approach. It is then possible to estimate the flow of votes between the first and the second round with very good precision and to provide the objective bases which will serve for an objective political or sociological analysis.